Civilian Strategy in Civil War Insights from Indonesia, Thailand, and the Philippines - Barter, Shane Joshua; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
While typically the victims of war, civilians are not necessarily passive recipients of violence. What options are available to civilians in times of war? This book suggests three broad strategies - flight, support, and voice. It focuses on three conflicts: Aceh, Indonesia; Patani, southern Thailand; and Mindanao, southern Philippines.
Keywords: Social sciences; Political science; Comparative politics; Anthropology; Ethnography; Sociology; Political sociology; Social Sciences; Ethnography; Comparative Politics; Political Sociology; Anthropology; Sociology, general; Political Science